Food industry information exchange and the role of meta-data and data lists. (1st January 2011) - Donnelly, Kathryn Anne-Marie; van der Roest, Joop; Höskuldsson, Stefán Torfi; Karlsen, Kine Mari; Olsen, Petter
To improve electronic communication between companies, universal standardised data lists are necessary. Food supply chain companies already record numerous measurements, properties and data elements. These records are necessary for legal reasons, labelling, traceability, profiling desirable characteristics, showing compliance and for meeting customer requirements. Universal standards for the name and content of each of these data elements would improve information exchange. Adequate provision of standardised data lists would also enable greater use of metadata and semantic technologies. A case study, carried out for the chicken sector, attempted to identify the most relevant data elements.